Three-phase extraction of polysaccharide from Stropharia rugosoannulata: Process optimization, structural characterization and bioactivities - Li, Xinxin; Zhang, Zhiqiang; Wang, Li; Zhao, Haoqiang; Jia, Yahui; Ma, Xia; Li, Jinzhan; Wang, Yi; Ma, Bingji (Frontiers in Immunology, 2023)
The isolation of Stropharia rugosoannulata polysaccharide (SRP) by three-phase extraction was optimized, and its structure and biological activities were identified. The optimal extraction conditions were: mass fraction of ammonium sulfate, 20%; volume ratio of sample solution to t-butanol, 1:1.5; extraction temperature, 35℃. Under these conditions, the yield of SRP was 6.85%±0.13%. SRP was found to be composed of glucose (35.79%), galactose (26.80%), glucuronic acid (9.92%), fructose (8.65%), xylose (7.92%), fucose (4.19%), arabinose (3.46%) and rhamnose (3.26%), with the molecular weight of 27.52 kDa. The results of DPPH, hydroxyl, ABTS+ radical scavenging and reducing power tests showed that SRP had good antioxidant capacities. SRP had no cytotoxic effect on RAW264.7 macrophages at the concentrations of 25-200 μg/mL, and could significantly promote phagocytosis activity and cell migration according to CCK-8 assay, phagocytosis assay and cell scratch experiment. SRP can significantly stimulate the transcript expression levels of TNF-α, IL-1β and IL-6, as determined by RT-PCR and Western blot assays. SRP activated the TLR4/NF-κB signaling pathway, and autophagy also occurred. These results suggest that SRP is a safe antioxidant and immunomodulator, and that it can be used in the development of functional foods and/or pharmaceuticals.